1999
DOI: 10.1021/cm9811040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cu2+ Ions on the Structure and Reactivity of Todorokite- and Cryptomelane-Type Manganese Oxide Octahedral Molecular Sieves

Abstract: The concentration effects on Cu uptake into the structures and reactivity of manganese oxide octahedral molecular sieves (OMS) were investigated. Two sets of 3 × 3-tunnel structure OMS designated as OMS-1 were synthesized by hydrothermal treatment at 160 °C for 48 h. The Cu-OMS-1 series of materials (tunnel substituted) were prepared by incorporating Cu 2+ ions into OL-1, which has a layered structure, at 60 °C for 24 h. [Cu]-OMS-1 materials (framework substituted) were prepared by ion exchanging Cu 2+ ions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 23 publications
3
31
0
7
Order By: Relevance
“…This phenomenon, also known as ''isomorphic substitution'', has been encountered by other researchers (Kanungo et al, 2004). Divalent cations, such as Ni(II) or Cu(II), can readily substitute for Mn(II) in the manganese oxide lattice to counterbalance the charge that develops during dissolution of Mn(IV) to Mn(III) and (II) (Nicolas-Tolentino et al, 1999). Although divalent heavy metals may follow this rule, the plots of Cu-Citrate complexes were non-linear.…”
Section: àmentioning
confidence: 87%
“…This phenomenon, also known as ''isomorphic substitution'', has been encountered by other researchers (Kanungo et al, 2004). Divalent cations, such as Ni(II) or Cu(II), can readily substitute for Mn(II) in the manganese oxide lattice to counterbalance the charge that develops during dissolution of Mn(IV) to Mn(III) and (II) (Nicolas-Tolentino et al, 1999). Although divalent heavy metals may follow this rule, the plots of Cu-Citrate complexes were non-linear.…”
Section: àmentioning
confidence: 87%
“…For example, partial exchange of K + ions in the OMS-2 tunnels with H 3 O + ions yielded excellent acid catalysts for selective oxidation reactions [12], while doping the framework with Co(II), Zr(II), Cu(II), W, Fe(III), and Cr(III), produced cryptomelane with novel morphologies and catalytic properties [13][14][15][16][17][18]. Incorporation pathways reported include solid-state conversion from metal doped birnessite [15], aqueous a priori incorporation using redox reactions [19], and ion-exchange techniques [20]. The first two methods lead to the formation of by-products, namely hausmannite, bixbytes, pyrolusite and nsutite, while the ion-exchange technique has the disadvantage of a lower replacement degree of K + ions in the tunnel structure.…”
Section: Introductionmentioning
confidence: 99%
“…The systematically lower dehydration temperatures of the Cu}M mixed formates as compared with those of the pure Mn, Co, and Ni formates from which they derive shows that incorporation of copper decreases the thermal stability of the structures: the copper ions that substitute for M> in these compounds could be considered as defects in the structure; a decrease in thermal stability has been recently observed in the manganese-containing oxides todorokite and cryptomelane, where it has been shown that the thermal stability of the crystal structures decreases as the amount of Cu that substitutes for Mn in the structure increases (10). On the other hand, the opposite tendency is observed when copper substitutes for zinc or cadmium in the structures of the pure cadmium or zinc dihydrated formates: the stability increases with the incorporation of copper in these structures, in good agreement with previous results for the Cu}Zn case (11).…”
Section: Discussionmentioning
confidence: 99%